2015
DOI: 10.1037/fsh0000140
|View full text |Cite
|
Sign up to set email alerts
|

Growing up with an ill parent: An examination of family characteristics and parental illness features.

Abstract: These findings extend our understanding of the impact of parental illness on late adolescents' psychosocial functioning. Results could have clinical applications for psychosocial interventions in children and families coping with chronic illness. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…This indicates that it is not su cient to distinguish between mental and physical illness in future studies, but also the degree of impairment by the physical illness. This is in line with the Stoeckel & Weissbrod [8] who found that greater impact of the parental illness was negatively correlated with adolescent's depression, anxiety, and life satisfaction.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This indicates that it is not su cient to distinguish between mental and physical illness in future studies, but also the degree of impairment by the physical illness. This is in line with the Stoeckel & Weissbrod [8] who found that greater impact of the parental illness was negatively correlated with adolescent's depression, anxiety, and life satisfaction.…”
Section: Discussionsupporting
confidence: 90%
“…Physical or mental illness may reduce the parental capacity [1] and result in role reversal, emotional and behavioral problems among the children, and lack of parent's attention [2][3][4]. Parental illness might even hamper the psychosocial development of the child and pose a potential risk to their mental and social functioning [5][6][7][8][9][10]. Moreover, parental illness have been associated with lower grade point average (GPA), higher risk of low educational achievement, and attenuated income in adulthood [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Items selected assessed relevant stressful experiences among young adults, including life-threatening illness or injury of a family member or close friend (Stoeckel and Weissbrod, 2015), accidents or death of a family member or close friend (Rostila et al, 2016), interpersonal events (e.g., break-up with a romantic partner, serious betrayal by someone other than one’s partner; Buitron et al, 2016), physical or sexual assault (Trotman et al, 2015; Viswanathan et al, 2014), and legal problems (e.g., time spent in jail; Salekin, 2008). …”
Section: Methodsmentioning
confidence: 99%
“…were assessed using 12 items taken from well-validated screeners, 3537 and included relevant stressful experiences among young adults, including life-threatening illness or injury of a family member or close friend 38 , accidents or death of a family member or close friend, 39 interpersonal events (e.g., break-up with a romantic partner, serious betrayal by someone other than one’s partner) 40 , physical or sexual assault, 41, 42 and legal problems (e.g., time spent in jail.) 43 …”
Section: Methodsmentioning
confidence: 99%